Exploring Gender Differences in Strategic Thinking: A Five-Dimensional Profiling Approach - Lichtarski, Janusz M.; Witek-Crabb, Anna; Mazurek, Edyta; Piórkowska, Katarzyna (Różnice płci w myśleniu strategicznym: profilowanie wielowymiarowe, 2025)
Aim: To identify gender differences in strategic thinking profiles using an original five-dimensional scale based on: the approach to change, the approach to the competitive environment, the information processing style, the level of participation and the level of flexibility. Methodology: Data from 184 Polish top managers and company owners were collected using a CAWI technique and analysed through PROFIT (Property Fitting) analysis. Results: The results reveal distinct strategic thinking profiles: women are more exploratory, relational and intuitive, whilst men are more analytical, competitive, and emergent. Women prefer an individualistic style during strategy formulation and a collective style during implementation, whereas men favour collaborative idea generation but top-down execution. Implications and recommendations: The findings suggest that gender diversity in top management teams broadens strategic perspectives and increases organisational resilience in diverse environmental conditions. One of the future research directions is to include representatives of different cultures. Another direction in future research is to use PROFIT analysis to identify differences in other variables, such as respondents' age and field of education, to understand the antecedents of strategic thinking. Originality/value: This study's contribution is to show gender diversity as a key to developing top teams with a broader perspective and more opportunities to build an effective strategy, and to use the PROFIT analysis which is not adequately popularised in management science.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 3, s. 77-93